Fatigue Risk Factors Of Offshore Oil And Gas Workers: A Systematic Review - Sinagabariang, Perkasa; Kurniawidjaja, L.Meily (Devotion : Journal of Research and Community Service, 2024)
Many offshore oil and gas workers experience fatigue due to shift work schedules, excessive working hours, lack of sleep, heavy workloads, and harsh environmental factors. Fatigue has the potential to impact an individual's performance, alertness, and overall health and safety. The objective of this research is to identify risk factors for fatigue in offshore oil and gas workers so that preventive measures can be taken. This research is a systematic review using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) to identify, select, and synthesize studies. Search via the central database, namely ScienceDirect. The publication period used is 2017-2024 with the keywords "Occupational Fatigue" AND "Offshore" AND "Oil and Gas". This research produced eight journals with a Q1 rating. The risk factors for fatigue in workers consist of four risk factors: environmental, organizational, psychosocial, and individual.